EVALUASI PERTUMBUHAN TANAMAN DARI BERBAGAI REGIONAL YANG DIBUDIDAYAKAN DI THHTI KALIMANTAN SELATAN - Lissa Anggraini; Gusti Muhammad Hatta; Normela Rachmawati (Universitas Lambung Mangkurat, 2023)
Plant growth is the process of increasing volume accompanied by an increase in the number of cells. The purpose of this study is to evaluate the growth of plants from various regions of Indonesia that are cultivated in THTTI Banjarbaru, South Kalimantan so that they can be used as consideration for further planting activities. Research implementation time for 3 months. Data were collected using purposive sampling method, the parameters in this study were the percentage of plant life, plant height and diameter. Based on the research results, it is known that in Kalimantan Region the percentage of plant life is 70% with an average height of 239.9 cm and a diameter of 28.5 mm, in the Java-Bali-Nusra Region the percentage of plant life is 100% with an average height of 230.1 cm and 43.12 mm in diameter, Sulawesi Region, the percentage of plant life is 93% with an average height of 228.7 cm and a diameter of 26.05 mm, Maluku Papua Region has a plant life percentage of 83% with an average height of 247.5 cm. and a diameter of 26.92 mm, and for the Sumatra Region the percentage of plant life was 100% with an average height of 246.3 cm and a diameter of 33.34 mm. The average plant growth is not uniform in each region, this happens because the species in each region are different so that the growth speed is not uniform, besides that many plants are disturbed and damaged by pests and weeds around the plantsPertumbuhan tanaman ialah proses pertambahan volume disertai pertambahan jumlah sel, Tujuan dari penelitian ini yaitu untuk mengevaluasi pertumbuhan tanaman dari berbagai regional Indonesia yang dibudidayakan di THHTI Banjarbaru Kalimantan Selatan sehingga dapat digunakan sebagai bahan pertimbangan untuk kegiatan penanaman selanjutnya. Waktu pelaksanaan penelitian selama 3 bulan. Pengambilan data dilakukan dengan menggunakan metode purposive sampling, parameter dalam penelitian ini yaitu persentase hidup tanaman, tinggi dan diameter tanaman. Berdasarkan hasil Penelitian diketahui bahwa pada Regional Kalimantan persentase hidup tanaman sebesar 70% dengan rata-rata tinggi 239,9 cm dan diameter 28,5 mm, Regional Jawa–Bali–Nusra persentase hidup tanaman sebesar 100% dengan rata-rata tinggi 230,1 cm dan diameter 43,12 mm, Regional Sulawesi persentase hidup tanaman sebesar 93% dengan rata-rata tinggi 228,7 cm dan diameter 26,05 mm, Regional Maluku Papua persentase hidup tanaman sebesar 83% dengan rata-rata tinggi 247,5 cm dan diameter 26,92 mm, dan Regional Sumatera persentase hidup tanaman sebesar 100% dengan rata-rata tinggi 246,3 cm dan diameter 33,34 mm. Rata-rata pertumbuhan tanaman tidak seragam pada setiap regional, hal ini terjadi karena jenis pada setiap regional berbeda sehingga kecepatan tumbuh pun tidak seragam, selain itu banyak tanaman yang terganggu dan mengalami kerusakan akibat hama serta gulma disekitar tanaman.